T-lymphocyte and inflammatory cell research in asthma - Jolles, G. (Georges); Karlsson, J.-A; Taylor, J. B. (John Bodenhan), 1939- (Academic Press, 1993)
It is well established that asthma is an inflammatory disease of the airway mucosa and drugs like inhaled glucocorticoids are now commonly introduced early in therapy. A characteristic feature of this disease is the vast number of eosinophils in airway tissue, although many other migratory and resident inflammatory cells with the capacity to synthesize and release cytokines and putative asthma mediators are present in the inflamed mucosa. The cross-talk between lymphocytes and these cells and the role of cytokines in complex biological networks are currently areas of intense research. This volume gathers together chapters and discussions on the biology of immunocompetent and inflammatory cells, cellular interplay and communication, and on the relative importance of cells and mediators in disease. It should help contribute to further insights into the pathology of asthma and to the development of novel efficacious drugs for the treatment of asthma and related respiratory disorders.